Eleocharis dulcis individually and in combination with Brassica rapa as a best cure of diabetes with zero side effects. Issue 9 (15th February 2022) - Arif, Asma; Gillani, Syeda Rubina; Hussain, Habib
Abstract: There is a lot of robust evidence of the use of various medicinal plants in lowering metabolic glucose levels in diabetic patients. The current study was designed to focus on the antidiabetic properties of Eleocharis dulcis and Brassica rapa . The stages carried out in this research are sample extraction, phytochemical analysis, FTIR analysis, proximate analysis, antioxidant, and clinical trial for antidiabetic activity. Twenty‐two male and female diabetic patients were selected from Lahore who was already taking the oral hypoglycemics drug. They were asked to take orally the equally mixed powder of both E. dulcis and B. rapa (almost 500 g) one time per day for 20 days. Blood glucose levels were assessed with the assistance of a glucometer. It was taken note that after utilizing the E. dulcis individually and in combination with B. rapa, blood glucose level was altogether decreased in both males and females. The current experiment and investigation established a pharmacological indication to support the traditional claim that B. rapa and E. dulcis are good antidiabetic agents. Novelty impact statement: The outcomes of this study back up previous studies on the effects of Brassica rapa and Eleocharis dulcis consumption on glucose control in diabetic patients. The findings of proximate and phytochemical studies of aqueous, hexane, and ethanolic extracts, as well as crushed powder demonstrated that both E. dulcis and Brassica rapa pulp contain a significant amount of nutrients.